2000
DOI: 10.1302/0301-620x.82b3.10193
|View full text |Cite
|
Sign up to set email alerts
|

The blood supply of the lateral epiphyseal arteries in Perthes' disease

Abstract: We performed superselective angiography in 28 hips in 25 patients with Perthes' disease in order to study the blood supply of the lateral epiphyseal arteries (LEAs). Interruption of the LEAs at their origin was observed in 19 hips (68%). Revascularisation in the form of numerous small arteries was seen in ten out of 11 hips in the initial stage of Perthes' disease, in seven of eight in the fragmentation stage and in five of nine in the healing stage. Penetration of mature arteries into the depths of the epiphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 0 publications
1
12
0
3
Order By: Relevance
“…Angiograms of children with Perthes' disease have revealed that, in early stages of the disease, there is a devascularization of the epiphysis most likely caused by an abrupt interruption of the medial circumflex artery (Théron, ; de Camargo et al, ). Furthermore, in children with Perthes' disease older than seven years old, there is an absence of a blood supply to the femoral head from the lateral circumflex and obturator arteries (Théron, ; de Camargo et al, ; Atsumi et al, ). This is followed by revascularization of the epiphysis, although the number of arteries supplying blood to the epiphysis of the afflicted side is reduced as compared to the contralateral side (de Camargo et al, ; Shore et al, ).…”
Section: Blood Supply To the Epiphysismentioning
confidence: 99%
“…Angiograms of children with Perthes' disease have revealed that, in early stages of the disease, there is a devascularization of the epiphysis most likely caused by an abrupt interruption of the medial circumflex artery (Théron, ; de Camargo et al, ). Furthermore, in children with Perthes' disease older than seven years old, there is an absence of a blood supply to the femoral head from the lateral circumflex and obturator arteries (Théron, ; de Camargo et al, ; Atsumi et al, ). This is followed by revascularization of the epiphysis, although the number of arteries supplying blood to the epiphysis of the afflicted side is reduced as compared to the contralateral side (de Camargo et al, ; Shore et al, ).…”
Section: Blood Supply To the Epiphysismentioning
confidence: 99%
“…We hypothesized that the assessment of the femoral head perfusion using MRI in the early stages of the disease would be informative, as a disruption of blood flow to the femoral head is a key pathogenic event producing osteonecrosis in LCPD. 14,[24][25][26][27][28][29] Various imaging studies have shown disruption of blood flow to the femoral head in LCPD. 14,27,30,31 The Conway classification, which uses bone scintigraphy, has been shown to have good value as a prognosticator of eventual disease severity, but has been shown to have only moderate interobserver and intraobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The precise cause of LCPD still eludes us, but it is clear that a vascular insult is the final precipitating episode that leads to the disease. [3][4][5][6] Studies on necropsy specimens suggest that Z2 infarcts precede the clinical onset of LCPD. 5,6 The blood supply to the capital femoral epiphysis during a period in childhood is solely from the lateral epiphyseal vessels and LCPD seems to develop at this time.…”
Section: The Natural History Of the Diseasementioning
confidence: 99%